Characteristics of Patients with Hypertension in Pregnancy at Sanglah Hospital - Hendrik Sutopo (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To report the profile of patients with Hypertension in Pregnancy (HIP) at Sanglah Hospital Denpasar from 2009 to 2010. Method: A retrospective descriptive study from all HIP patients at Sanglah Hospital Denpasar, Bali during January 2009 to December 2010. Result: The prevalence of HIP at Sanglah Hospital was 9.32%, which consisted of 1.82% gestational hypertension, 0.19% chronic hypertension, 1.36% mild preeclampsia, 4.70% severe preeclampsia, 0.43% superimposed preeclampsia, and 0.82% eclampsia. From all of HIP cases, we found that the majority were nulliparous (47.23%), primipaternal (53.1%), and had hypertension at term (51.9%). Most of the cases were found at maternal age > 35 years (14.62%), followed by age < 20 years (13.47%). Most of them also had Ante Natal Care (ANC) frequency â‰¥ 4 times (69.09%), and had their ANC done by a midwife (52.76%) and followed with an obstetrician (40.81%). The majority of the cases were referral cases (62.39%) mostly by midwives (22.45%). From all of the cases, we found that total preterm labor was 35.14%, perinatal mortality was 9.32% and maternal mortality was 1.16%. Conclusion: The prevalence of HIP at Sanglah Hospital was higher than previous years. Most of them had already had ANC done by health care providers, who were mostly midwives and obstetricians. Therefor, the quality of ANC seems to need an improvement by having an earlier referral system, so cases can be treated earlier. [Indones J Obstet Gynecol 2011; 35-3: 97-9] Keywords: hypertension in pregnancy, preeclampsia and eclampsia, descriptive